Taking it to scale insights from IFPRI's research on improving nutrition behaviors in multiple contexts - Lapping, Karin (2017)
Karin Lapping IFPRI and Alive & Thrive Policy Seminar Taking It to Scale: Insights from IFPRI’s Research on Improving Nutrition Behaviors in Multiple Contexts June 28, 2017 - 12:15 PM TO 01:45 PM EDT